Minor injury and minor illness at a glance - Morris, Francis; Wardrope, Jim; Ramlakhan, Shammi (At a glance series., 2014)
This brand new title provides a highly illustrated and unambiguous introduction to most common presentations encountered in GP surgeries, in minor injury units and emergency departments. It provides the basic information required to identify and manage these conditions, as well as highlighting the pitfalls and the key diagnoses not to be missed. Minor Injury and Minor Illness at a Glance: Presents the perfect combination of text and image; double page spreads enable quick access to information for readers in a pressurised environment Covers a wide range of.